2015
DOI: 10.3945/ajcn.114.088948
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid composition of adipose tissue and colorectal cancer: a case-control study

Abstract: CRC patients presented higher concentrations of some FAs but lower concentrations of α-linolenic acid in their subcutaneous adipose tissue than did controls. These results may reflect both dietary patterns and altered FA metabolism but require mechanistic explorations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 48 publications
1
28
0
3
Order By: Relevance
“…Dietary fats are associated with a higher risk of developing colorectal cancer; in fact, a direct association between the intake of trans fatty acids and cancer has been found [10]. Increased concentrations of longchain fatty acids (LCFA) also seem to be associated with an increased risk of CRC [11]. For these reasons, many researchers have focused their attention on possible associations between CRC progression and alterations in lipid levels.…”
Section: Introductionmentioning
confidence: 98%
“…Dietary fats are associated with a higher risk of developing colorectal cancer; in fact, a direct association between the intake of trans fatty acids and cancer has been found [10]. Increased concentrations of longchain fatty acids (LCFA) also seem to be associated with an increased risk of CRC [11]. For these reasons, many researchers have focused their attention on possible associations between CRC progression and alterations in lipid levels.…”
Section: Introductionmentioning
confidence: 98%
“…[8] In contrast, DHA in the plasma has shown positive correlation with tumorogenesis and development of CRC, [9] while ALA found in subcutaneous adipose tissues has displayed a negative correlation with CRC risk. [10] In addition, tumor tissues display decreased LA and increased DHLA levels, compared with surrounding normal tissues. [11] Furthermore, some additional studies have reported that administration of PUFAs (polyunsaturated fatty acids) and n-3 PUFA prevented the occurrence of gastric and CRC, while SFA and n-6 PUFA promoted development of such malignancies.…”
Section: Introductionmentioning
confidence: 99%
“…Although no dietary information was available for the study population, the low ω3/ω6 PUFA ratio generally observed in AT likely reflects Western dietary habits [74] . Changes in the ω3/ω6 PUFA profile (higher dihomo-γ-linolenic and docosapentaenoic acids, vs. lower α linolenic acid) were also reported in SAT from CRC patients, in association with markers of systemic inflammation [75] . The altered ω3/ω6 PUFA balance in cancer patients can markedly affect tissue composition and function as a result of the reduced protective effect of ω3 PUFA.…”
Section: Adipose Tissue Inflammation Fatty Acid Profile and Colorectmentioning
confidence: 82%
“…More recently, a general agreement has been achieved on the increased accumulation of pro-inflammatory ω6 PUFA (mostly dihomo-γ-linolenic and arachidonic acids) as well as on the unbalanced ω3/ω6 PUFA ratio in the AT of CRC patients, regardless of tumor subsite, even though differences were reported among studies on the relative abundance of individual PUFA and type of AT involved [27,[73][74][75] . In particular, a comparison of VAT and SAT FA profiles in colon cancer (CC) patients highlights a decrease of the ω3 PUFA α linolenic and stearidonic acid content, coupled to increased dihomo-γ-linolenic and arachidonic acid content in VAT of CC patients as compared to controls.…”
Section: Adipose Tissue Inflammation Fatty Acid Profile and Colorectmentioning
confidence: 94%